2021
DOI: 10.1183/23120541.00915-2020
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar macrophage transcriptomic profiling in COPD shows major lipid metabolism changes

Abstract: BackgroundImmune cells play a major role in the pathogenesis of chronic obstructive pulmonary disease (COPD). Albeit established changes in distribution and cellular functions of major immune cells, such as alveolar macrophages (AMs) and neutrophils, their transcriptional reprogramming and contribution to the pathophysiology of COPD are still not fully understood.Aim and methodsTo determine changes in transcriptional reprogramming and lipid metabolism in the major immune cell type within the bronchoalveolar la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 66 publications
4
24
2
Order By: Relevance
“…19,51,57,58 . In contrast to a recent study of the COPD alveolar macrophage transcriptome 48 , we did not see signs of altered lipid metabolism in alveolar macrophage expression signatures. However, this previous study included more severe and predominantly smoking COPD patients, which may explain differences with our observations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…19,51,57,58 . In contrast to a recent study of the COPD alveolar macrophage transcriptome 48 , we did not see signs of altered lipid metabolism in alveolar macrophage expression signatures. However, this previous study included more severe and predominantly smoking COPD patients, which may explain differences with our observations.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study in Cd44-/-knockout mice, demonstrated that deficiency of CD44 on alveolar macrophages, disrupted surfactant lipid homeostasis 44 . We analysed the transcriptome of purified BAL macrophages (demographics for included participants given in Table S3) and found no significant activation of transcriptomic pathways involved in macrophage lipid turnover or potentially involved in surfactant metabolism using either differentially expressed gene (DEG) analysis or WGNCA (Figure S3) 48 .…”
Section: Alveolar Macrophage Gene Expressionmentioning
confidence: 99%
“…Disorders of pulmonary lipid metabolism are a well-known pathophysiological characteristic of the processes that are associated with the progression of COPD [ 180 , 207 ]. These changes affect predominantly macrophages, thus providing a close link between impaired pulmonary lipid metabolism and the innate immune response [ 178 ].…”
Section: Lipid Metabolism Disorders In the Development And Progression Of Copdmentioning
confidence: 99%
“…In response to inflammatory stimuli, AMs secrete cytokines and chemokines to initiate the immune response. Subsequently, AMs and recruited monocytes contribute to the resolution of the inflammatory response to prevent excess damage ( Janssen et al, 2011 ; Mould et al, 2017 ; Fujii et al, 2021 ; Hetzel et al, 2021 ). In addition, they play a major role in maintaining lipid homeostasis in the lung, which is essential for adequate gas exchange and alveolar epithelial integrity.…”
Section: Introductionmentioning
confidence: 99%